A controllable inductive power filtering system: modeling, analysis and control design. (February 2019) - Liu, Qianyi; Li, Yong; Hu, Sijia; Luo, Longfu
Highlights: Establishing the three-phase equivalent mathematical model for CIPF. Revealing the distinctive operational mechanism of the CIPF method in a mathematical sense. Finding out the operational law. An improved control strategy is designed. Abstract: This paper presents a controllable inductive power filtering (CIPF) system with the novel filtering mechanism. Due to the zero-impedance design of the power transformer, the harmonic magnetic flux between the secondary load winding and the customized filtering winding can be balanced each other. Hence, the contaminated area of harmonics is reduced. The addition of the active filter contributes to further improve the filtering performance with the task of harmonic isolation between the power grid and the load. First, the three-phase unified equivalent circuit model and the mathematical model are given out at the harmonic domain. Based on the deduced transfer matrix, the filtering evaluation criterion of CIPF system is established, and the filtering principle is revealed, as well. According to the special operational law, an improved virtual impedance control strategy is designed to prevent the potential harmonic amplification, and the relationship between the phase/magnitude of the virtual impedance and the filtering performance is discussed. Finally, the experimental results based on the laboratory scaled prototype show the validity of the CIPF system with improved virtual impedance control.